The Effect of Psychological Wellbeing and Employee Integrity on Organizational Commitment by Mediating Organizational Change in Employees BNI Surabaya Commercial Business Center - Anita Rahmawati; Nuri Herachwati (PT Mattawang Mediatama Solution, 2024)
Organizational commitment has an important role in maintaining employee loyalty to work for a company with various applicable regulations. However, many employees are found who are not committed to the organization, so this should be a concern for the company because commitment is closely related to employee performance. The aim of this research is to analyze the influence psychological wellbeing on organizational commitment, analyzing the influence of employee integrity on organizational commitment, analyzing the influence psychological wellbeing on organizational commitment by mediating organizational change, analyzing the influence of employee integrity on organizational commitment by mediating organizational change and to analyze the influence of organizational change on organizational commitment. This research is qualitative research with a comparative causal design. The data collection method was carried out through distributing questionnaires. The sampling method used purposive sampling, with criteria employee with permanent employee status and has a minimum service period of 1 (one) year, because he has participated in the organizational change process that occurred at the BNI Commercial Business Center in Surabaya and is still an active employee of the BNI Commercial Business Center in Surabaya. This research data analysis uses Structural Equation Modeling (SEM)Partial Least Square (PLS). Based on the description in the discussion above, it can be concluded that psychological wellbeing has a positive and significant effect on organizational commitment, employee integrity has a positive and significant effect to organizational commitment, psychological wellbeing positive and significant effect on organizational commitment by mediating organizational change. Indirect influence psychological wellbeing towards organizational commitment through organizational change is 0.335, which means of psychological wellbeing increasing by one unit, organizational commitment can increase directly and indirectly through organizational changes by 72.1%. This influence is positive. Employee integrity influences organizational commitment by mediating organizational change. The total influence of employee integrity on organizational commitment is 0.388, which means that if employee integrity increases by one unit, organizational commitment can increase directly and indirectly through organizational changes by 25.9% and organizational changes have no effect on organizational commitment